Intervensi Komitmen Dalam Memperkuat Pengaruh Pelatihan, Supervisi dan Lingkungan Terhadap Kinerja - Farrasoya, Maitsa; Hariyanto, Eko; Astuti, Herni Justiana; Amir, Amir (Widya Cipta - Jurnal Sekretari dan Manajemen, 2023)
Perawat adalah salah satu anggota terpenting dari staf rumah sakit. Karena perawat adalah yang paling terlihat oleh pasien, kinerja perawat akan menggambarkan kinerja rumah sakit. Penelitian ini bertujuan untuk menganalisis dampak dari pelatihan, supervise, lingkungan terhadap kinerja perawat dengan komitmen sebagai variable intervening. Penelitian dilakukan secara kuantitatif dengan jumlah sampel diambil secra sensus dari populasi yang tersedia yaitu 96 perawat di RSI Purwokerto. Pengumpulan data menggunakan kuesioner yang dibagikan menggunakan google form kemudian dianalisis menggunakan SEM PLS. Hasil penelitian menujukkan bahwa pelatihan yang diselenggarakan mampu meningkatkan kinerja, supervisi dari kepala ruangan juga meningkatkan kinerja dan lingkungan juga turut mempengaruhi kinerja. Komitmen mampu menjadi variable intervening pengaruh dari pelatihan supervisi, lingkungan terhadap kinerja The nurse is one of the most important members of the hospital staff. Since nurses are the most visible to patients, nursing performance will describe hospital performance. The performance of nurses is part of the values that are important for patients in the quality of hospital services. Because of different perceptions of nurses’ performance, comments and protests from patients’ families who are dissatisfied with hospital services still occur over time, but it is difficult to prove the authenticity of such events and comments. The role of training, supervision, environment, and commitment is important for improving the performance of nurses. The study aims to analyze the impact of training, supervision, and environment on the performance of nurses, with commitment as an intervening variable. The study was carried out quantitatively with the number of samples taken during the direct census from the available population of 96 nurses in RSI Purwokerto. Data collection using a questionnaire shared using Google Forms is then analyzed using SEM PLS. The results of the research indicate that the training organized can improve performance; supervision from the head of the room also improves performance; and the environment also affects performance. Commitment can be a variable influenced by the intervening influences of training, supervision, and environment on performance. Thus, to improve the performance of nurses, training should be done frequently, supervision of the leadership should be performed well, the working environment should be improved, and commitment should be increased.